Calcium Carbonate Induced Precipitation for Soil Improvement by Urea Hydrolysing Bacteria - Dekuyer, A.; Cheng, L.; Shahin, Mohamed; Cord-Ruwisch, R. (Techno-Press, 2012)
Existing methods for improving the engineering properties of soils are diverse with respect to their final outcome. Grouting by chemical additives is currently one of the most commonly used soil stabilization techniques; however, it may have some environmental, reproducibility and health concerns. These drawbacks and the increasing population in regions of limited land drive the need to develop new technologies for ground improvement. The aim of this work is to introduce and examine a newly emerging microbiological process, known as microbial induced calcite precipitation (MICP), for soil stabilization. MICP is a promising technique that utilizes the metabolic pathway of bacteria to form calcite precipitation throughout the soil matrix, leading to an increase in soil strength and stiffness. The study investigates the geotechnical properties of bio-cemented silica sand under different degrees of saturation at which bio-cementation occurs. A series of laboratory experiments are conducted including the sieve analysis, permeability, unconfined compression strength and consolidated undrained tri-axial tests. The results confirm the potential of MICP as a viable alternative technique that can be used successfully for soil improvement in many geotechnical engineering applications, including liquefaction of sand deposits, slope stability and subgrade improvement. The results also indicate that higher soil strength can be obtained at lower degrees of saturation, negating the belief that bio-cemented soils need to be treated under full saturation conditions.